Analysis of Fornax-like clusters in numerical simulations and its comparison with Fornax cluster data obtained with S-PLUS - Zenocratti, Lucas Jesús (2023)
Using photometric data in 12 optical bands obtained within the S-PLUS collaboration, and withthe goal of studying in detail the Fornax cluster of galaxies, the Fornax project (S+FP) was defined in that collaboration. In the framework of this project, and as a continuation of a previous work, we analyze Fornax-like candidates extracted from the eagle (RefL0100N1504 model) and the illustris-tng (TNG100-1 and TNG300-1 models) cosmological numerical simulations, selecting them according to observed features in the Fornax cluster. In this contribution, we present the comparison between the main characteristics of the selected clusters and those observed in Fornax, with improvements in both our simulated clusters selection criteria, and in the implementation of the code we use to generate simulated quantities that can be directly compared with observations. Among other properties, we plan to compare the morphologies of the simulated galaxies in the selected clusters with thosedisplayed by the galaxies in Fornax.